Structured report improves radiology residents’ performance in reporting chest high-resolution computed tomography: a study in patients with connective tissue disease - Lorenzo Cereser; Filippo Marchesini; Emma Di Poi; Luca Quartuccio; Alen Zabotti; Chiara Zuiani; Rossano Girometti (Diagnostic and Interventional Radiology, 2022)

(untitled)
PURPOSETo evaluate the performance of radiology residents (RRs) when using a dedicated structured report (SR) template for chest HRCT in patients with suspected connective tissue disease-interstitial lung disease (CTD-ILD), compared to the traditional narrative report (NR).METHODSWe retrospectively evaluated 50 HRCT exams in patients with suspected CTD-ILD. A chest-devoted radiologist reported all the HRCT exams as the reference standard, pointing out pulmonary fibrosis findings (i.e., honeycombing, traction bronchiectasis, reticulation, and volume loss), presence and pattern of ILD, and possible other diagnoses. We divided four RRs into two groups according to their expertise level. In each group, RRs reported all HRCT examinations alternatively with NR or SR, noting each report's reporting time. The Cohen's Kappa, Wilcoxon, and McNemar tests were used for statistical analysis.RESULTSRegarding the pulmonary fibrosis findings, we found higher agreement between RRs and the reference standard reader when using SR than NR, regardless of their expertise level, except for volume loss.RRs' accuracy for "other diagnosis" was higher when using SR than NR, moving from 0.48 to 0.66 in the novel group (p = 0.035) and from 0.44 to 0.80 in the expertise group (p < 0.001). No differences in accuracy were found between ILD presence and ILD pattern. The reporting time was significantly lower (p = 0.001) when using SR than NR.CONCLUSIONSR is of value in increasing the reporting of critical chest HRCT findings in the complex CTD-ILD scenario and should be used early and systematically during the residency.